Dividends and Attention: Herding, Neglect, and Distraction Among Indonesian Retail Investors - Kesuma, Wendy (Keizai, 2025)
This study explores retail investor behavior in the context of dividend events by testing three interrelated hypotheses: the dividend-herding hypothesis, the neglected firm hypothesis, and the divided attention hypothesis. Utilizing the Google Search Volume Index (SVI) as an innovative proxy for measuring retail investor attention, the study analyzes 642 dividend events in the Indonesian stock market. The empirical findings support all three hypotheses. First, retail investors demonstrate limited attention to dividend-paying stocks, despite extensive evidence of positive price reactions, suggesting a herding pattern driven by inattention. Second, dividend announcements serve as attention-grabbing events that increase visibility for previously overlooked or neglected firms. Third, when multiple companies announce dividends on the same trading day, retail investor attention becomes fragmented, resulting in reduced focus on individual stocks. These findings offer new insights into behavioral finance in emerging markets and highlight the importance of investor attention in understanding market reactions to corporate events.